MONITORIZAREA ÎN CONTEXTUL AUTOREGLĂRII ACADEMICE - USM ADMIN (Moldova State University, 2011)
The purpose of the present article is the reasoning approach: self-monitoring and self-control capacities provide the student's academic independence and quality of the learner-centered education. In this sense, we present a framework for understanding the concept of "monitoring learning" as a general term and as essential process of self-regulated learning. In particular, corollary monitoring differentiated terms are: self-monitoring, evaluation / self-evaluation, feedback / self- feedback, goals, and their operating mechanisms in academic learning.